KEARIFAN LOKAL MASYARAKAT ADAT DAYAK HIBUN DALAM MELESTARIKAN HUTAN TERINGKANG DI DUSUN BERUAK DESA GUNAM KECAMATAN PARINDU KABUPATEN SANGGAU - Prameswari, Sely Indri; M, Iskandar A; Rifanjani, Slamet (Universitas Tanjungpura, 2019)
Dayak hibun people cannot be separated from the forest in their daily lives. they maintain the preservation of the surrounding forest, one of which is the caged forest. The research aimed to collect information regardingthe local wisdomPublicDayak Hibun Â in Beruak, Gunam Village, Parindu Subdistrict, Sanggau Regency, in an effort to preserve the teringkang forest. The research method using survey method, and the technique of data collection was snowball sampling. The data was obtained through a depth-interview and interview guideline as a reference. The results of the data analysis show that there are several forms of local wisdom practiced in gunam village, namely 1. (a) prohibition of cutting down the trees, (b) opening the Teringkang forest for farming, (c) burning goods such as shrimp paste and fish, (d) taking and killing animals, (e) urinating and defecating in the Teringkang Forest, 2. belief in the presence of Bunyik (ghosts), having rituals entering the Teringkang Forest, and Keeping words politeness, 3. Hence the community has belief in mystical matters, 4. Therefore, the Teringkang Forest is still preserved up until today.Keywords: Dayak Hibun, Local Wisdom, Teringkang Forest